Exploring the Impact of Green Servant Leadership on Organizational Sustainability: A Comprehensive Analysis of Employee Engagement, Behavior, and Business Performance - Moh. Hamzah; Rini Aristin; Imadoeddin Imadoeddin; Winanda Dyah Mufida; Aisyah Dwi Yunita; Zainurrafiqi Zainurrafiqi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study explores the impact of Green Servant Leadership (GSL) on the Sustainable Business Performance of small and medium-sized enterprises (SMEs), with a focus on its influence through two mediating variables: Green Work Engagement (GWE) and Green Self-Efficacy (GSE). Conducted in Pamekasan, Indonesia, the research seeks to examine how Green Servant Leadership can promote organizational sustainability by fostering employee engagement in environmentally friendly practices and enhancing individual self-efficacy in performing green behaviors. A quantitative approach, using surveys from 199 SME managers in Pamekasan, was employed to collect data, which was analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using WarpPLS software. This study investigates the relationships between GSL, GWE, GSE, Employees' Workplace Green Behavior (EWGB), and Sustainable Business Performance to provide insights into how leadership and employee engagement can drive sustainable business practices in SMEs. The findings reveal that Green Servant Leadership positively influences Green Work Engagement and Employees' Workplace Green Behavior but does not significantly impact Green Self-Efficacy or Sustainable Business Performance. The research highlights the complex interplay between leadership styles, employee engagement, and environmental behaviors, offering valuable guidance for SME leaders aiming to integrate sustainability into their business strategies.